PENGARUH TEKNIK MOZAIK TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK USIA PRASEKOLAH DI DESA PONDOK BULUH KECAMATAN DOLOK PANRIBUAN KABUPATEN SIMALUNGUN TAHUN 2023 - Utary Dwi Listiarini; Indah Dewi Sari; Ani Deswita Chaniago; Itasari Erjawanty Manik (Jurnal Maternitas Kebidanan, 2024)
The World Health Organization (WHO) reports that 5-25% of preschool children suffer from minor brain dysfunction, including impaired fine motor development. About 9% of children experience anxiety disorders, 11-15% are easily emotional, 9-15% are behavioral disorders. Around 16% of toddlers in Indonesia are reported to experience developmental disorders in the form of intelligence disorders due to brain development disorders, hearing problems and motor disorders. Impaired growth and development in children in Indonesia is classified as a major public health problem. The aim of the research is to determine the influence of the mosaic technique on the fine motor development of preschool-age children in Pondok Buluh Village, Dolok Panribuan District, Simalungun Regency in 2023. This research design is Quasi Experimental with one group pre test post test. The total population, namely all preschool children in Pondok Buluh village, Dolok Panribuan District, Simalungun Regency, was 25 people and the sample used accidental sampling, namely 17 respondents. The data used uses primary and secondary data. Data analysis using univariate and bivariate using non-parametric samples with mosaic technique tests has an influence on the motoric development of preschool children in Pondok Buluh Village, Dolok Panribuan District, Simalungun Regency.The research results were obtained using the T test with results showing sig-α 0.000 < 0.05. The mosaic technique has an influence on the motor development of preschool children in Pondok Buluh Village, Dolok Panribuan District, Simalungun Regency. The conclusion is that there is an influence of the mosaic technique on the motor development of preschool children in Pondok Buluh Village, Dolok Panribuan District, Simalungun Regency in 2023. It is hoped that pregnant women will seek information about the importance of prenatal check-ups at least 6 times during pregnancy. Keywords : Mosaic, motor development, pre-school children